Validasi Bahan Ajar Fisika Berbasis Pembelajaran Inkuiri pada Materi Pelajaran Usaha, Energi, Momentum, Impuls dan Tumbukan untuk Meningkatkan Kemampuan Berpikir Kreatif - Risky Wahyuni; Hufri Hufri; Harman Amir (Universitas Negeri Padang, 2018)
Learning according to the 2013 curriculum requires teachers to develop the quality of learning, especially in the use of teaching materials of physics learning. By using teaching materials students are more able to learn independently according to the activities in these teaching materials. The purpose of this research is to design the instructional materials based on inquiry, to find out the design of the inquiry-based teaching materials and the value of validity. Inquiry-based teaching materials can develop students' mindsets so that students can find concepts or materials learned so that students can shape their thinking skills. Type of research used is Research and Development (R & D) The object of this study is teaching materials based on inquiry. Based on data analysis obtained from 2 research. The first is the design of instructional materials based on inquiry. The second, the average value of expert validity with a value of 88 with criteria is very valid. It can be concluded that inquiry-based teaching materials have high scores with very valid categories for use in teaching physics class X SMA